The Goal of Business-A Review Paper (Global Journal of Management and Business Research, 2016)
The main aim of business is to fulfill the need of the human beings to create a harmony. Though this aim is debatable right since its origin. The scholars defines the goals of business in their studies differently. A numerous studies evaluated the concept of sustainable business and its social responsibility towards society and the nature. Wheeler & McKague (2002) evaluates the role of the business in development and evaluates the function and responsibility of the NGOs, development agencies and government in the same. The study also evaluates the Social-Global Economic Trends. Nelson & Prescott (2003) inspects the role of Business and its role in the Millennium development of the world society. Study attempts the questions that what are the business goals how are they relevant and how the business can achieve them. Fitzgerald KBE & Mandy Cormak (2005), Modesto & Oliveira (2006) & Terziev (2012), attempts to investigate the role of the business organizations in the society and their social responsibility towards.
Keywords: attempts to investigate the role of the business organizations